A flexible multiferroic composite with high self-biased magnetoelectric coupling. (1st December 2017) - Jing, W.Q.; Fang, F.
Abstract: Polymer-matrix multiferroic composites with self-biased magnetoelectric (ME) coupling hold promises in flexible energy harvester, magnetic field sensors and actuators, etc. Using CoFe2 O4 (CFO) nanoparticles and multi-walled carbon nanotubes (CNTs) as fillers to the polyvinylidene fluoride (PVDF) matrix, piezomagnetic films (CFO-CNT-PVDF, also named as M layers) with different volume fractions of CFO and a fixed percentage of CNTs are obtained, which also serve as the electrode. By employing the layer of poly(vinylidene fluoride-trifluoroethylene) (P(VDF-TrFE), named as P layer) sandwiched between the two conductive layers of CFO-CNT-PVDF, and followed by hot-pressing, three-layered multiferroic composite CFO-CNT-PVDF/P(VDF-TrFE)/CFO-CNT-PVDF (named as M / P /M) are prepared. The ME coupling increases with the volume fraction of CFO nanoparticles. The maximum self-biased and peak values of ME coefficient ( α ME ) reach 16.7 mV cm −1  Oe −1 and 25.8 mV cm −1  Oe −1, respectively. Measurements on the relationship between the magnetostriction and static magnetic field ( H s ) are performed for the CFO-CNT-PVDF films with different volume fraction of CFO. Based on the equivalent circuit model, the self-biased and peak values of α ME are calculated for the ME composites, which fit well with the experimental data. The results imply that it is the high piezomagnetic coefficient, as well as the remnant magnetization of the M layer, contributes to the observed strong self-biased ME coupling for the CFO-CNT-PVDF/P(VDF-TrFE)/CFO-CNT-PVDF composite. Since the mechanical flexibility is also of great importance regarding the practical device applications, the stress-strain behavior for the CFO-CNT-PVDF layers is studied. With the volume fraction of CFO increases, both fracture strength ( σ f ) and fracture strain ( ε f ) decrease. The results offer a guideline for selecting proper ME composites on specified device applications.